Spatial behavior in dynamical thermoviscoelasticity backward in time for porous media. Issue 12 (1st December 2016) - Bucur, Andreea
ABSTRACT: In this article we study the spatial behavior of solutions to the backward in time problem associated with the linear theory of thermoviscoelastic materials with voids. We consider an appropriate time-weighted volume measure associated with the final boundary value problem and then, in terms of such measure, we obtain a first-order partial differential inequality. Some spatial estimates of Saint-Venant type are established.